Optimalisasi Penerapan Literasi Digital pada Pendidikan Sepanjang Hayat - Yulia Agustina; Hary Murcahyanto (Journal of Elementary School (JOES), 2023)
This research aims to describe the stages of learning in the concept of lifelong education, the role of education in lifelong education, building interest in digital literacy in learning, and realizing lifelong education through digital literacy skills. This research uses a qualitative descriptive method. The data used were the results of observations and interviews taken randomly in several primary and secondary schools in the East Lombok district. Data triangulation: observation, interviews, and documentation were used in data collection and data verification. The interactive model was used to analyze the data using data collection, data compaction, data presentation, and conclusion drawing. The results of this study are that the stages of the concept of lifelong education do not only occur in formal environments but in informal and non-formal environments. The role of language education in lifelong education is that the more a person studies and learns a language well, the better the cultural principles that will be held. Building interest in digital literacy in language learning by getting used to reading in assignments using electronic equipment. Efforts to realize lifelong education through digital literacy skills by promoting learning independence among fellow community members as a parameter of sustainable social development. Keywords: digital literacy, interest in learning, lifelong education